D2D sub-THz Industrial Radio System for 6G Use Case Definition RF Transceiver Requirements Analysis and Feasibility Considerations - Fink, Lucas; Seifaei, Masoud; Benzin, Andreas; Osterland, Dennis; Franchi, Norman (European Wireless 2024, 2024)
In industrial environments, it is necessary to transfer data between sensors, actuators, and control units with high data rates and low latency. The development of the sixth generation (6G) of mobile communications enables new frequency bands like D-band (110–170 GHz) for wireless transmission in the sub-terahertz (sub-THz) range. In this frequency range, ultra-broadband transmission enables high throughput between robots and machines in production plants using a wireless link. This work introduces a high-throughput short-range point-to-point use case for sub-THz communications systems in an industrial environment to enhance or replace wired industrial fieldbus and Industrial Ethernet networks. The aim is to make industrial communications networks more flexible, using the high transmission capacity to increase data rates and decrease latency by implementing D2D communications. After defining the use case, requirements for the hardware components of a sub-THz transceiver including a phased array antenna are investigated. The path loss is calculated depending on predefined link distance, SNR at the receiver, achievable data rate, and minimum signal integrity at the ADC are determined using state-of-the-art transceiver system specifications. With the results, a statement about the principle feasibility of the use case is made based on the specifications of a state-of-the-art sub-THz radio system.<br
Keywords: 6G; digital twin; industry 4.0; Industrial Ethernet; sub-terahertz; wireless communications

Experimental and Simulative Characterization of a Hybrid Magnetic Array for Steering Superparamagnetic Nanoparticles in Drug Targeting - Thalmayer, Angelika; Fink, Lucas; Fischer, Georg (IEEE Transactions on Biomedical Engineering, 2025)

German Perspective on 6G – Use Cases, Technical Building Blocks and Requirements Insights by the 6G Platform Germany - Franchi, Norman; Dressler, Falko; Ergenc, Doganalp; Guter, Paulus; Lassen, Vincent; Lübke, Maximilian; Veihelmann, Christian Tobias; Baradie, Shaden; Bassbouss, Louay; Bathelt, Andreas; Eichhorn, Fabian; Fink, Lucas; et al. (FAU University Press, 2024)